Les parents et les déplacements entre la maison et l’école primaire : quelle place pour l’enfant dans la ville ? - Paul Lewis; Juan Torres (Enfances, Familles, Générations, 2010)
The urban structure and organization of the school system impact children’s mobility and more specifically their modes of travelling to and from school. These are affected to a similar extent by parental habits, perceptions and choices. The present article deals with the relationship between parental considerations and behaviours on the one hand and the modes of transportation governing the movement of children from home to school and back again on the other. This study is based on a survey carried out by the Groupe de recherche ville et mobilité, involving 1495 parents of primary level pupils (French-language and English- language public and private sector schools) in Montreal and Trois-Rivières between 2006 and 2008. A linkage will be observed between the forms of transportation used by school children and parental representations with regard to neighborhood safety and the importance of active transportation. Linkage will also be observed between the parents’ and the children’s modes of transportation to and from school.